Risky Decision Making Under Stressful Conditions: Men and Women With Smaller Cortisol Elevations Make Riskier Social and Economic Decisions - Dreyer, Anna J.; Stephen, Dale; Human, Robyn; Swanepoel, Tarah L.; Adams, Leanne; O'Neill, Aimee; Jacobs, W. Jake; Thomas, Kevin G. F. (Frontiers in Psychology, 2022)
Men often make riskier decisions than women across a wide range of real-life behaviours. Whether this sex difference is accentuated, diminished, or stable under stressful conditions is, however, contested in the scientific literature. A critical blind spot lies amid this contestation: Most studies use standardized, laboratory-based, cognitive measures of decision making rather than complex real-life social simulation tasks to assess risk-related behaviour. To address this blind spot, we investigated the effects of acute psychosocial stress on risk decision making in men and women (N = 80) using a standardized cognitive measure (the Iowa Gambling Task; IGT) and a novel task that simulated a real-life social situation (an online chatroom in which participants interacted with other men and women in sexually suggestive scenarios). Participants were exposed to either an acute psychosocial stressor or an equivalent control condition. Stressor-exposed participants were further characterized as high- or low-cortisol responders. Results confirmed that the experimental manipulation was effective. On the IGT, participants characterized as low-cortisol responders (as well as those in the Non-Stress group) made significantly riskier decisions than those characterized as high-cortisol responders. Similarly, in the online chatroom, participants characterized as low-cortisol responders (but not those characterized as high-cortisol responders) were, relative to those in the Non-Stress group, significantly more likely to make risky decisions. Together, these results suggest that at lower levels of cortisol both men and women tend to make riskier decisions in both economic and social spheres.